2017
DOI: 10.1093/mnras/stx847
|View full text |Cite
|
Sign up to set email alerts
|

Core shift effect in blazars

Abstract: We studied the pc-scale core shift effect using radio light curves for three blazars, S5 0716+714, 3C 279 and BL Lacertae, which were monitored at five frequencies (ν) between 4.8 GHz and 36.8 GHz using the University of Michigan Radio Astronomical Observatory (UMRAO), the Crimean Astrophysical Observatory (CrAO), and Metsahovi Radio Observatory for over 40 years. Flares were Gaussian fitted to derive time delays between observed frequencies for each flare (∆t), peak amplitude (A), and their half width. Using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 82 publications
3
20
0
Order By: Relevance
“…It has also been categorized as an optically violent variable (OVV) revealing large and rapid polarized outbursts in optical bands on various timescales (days to years). Multifrequency radio light curves (4.8 have been used to study the core shift effect and to estimate the equipartition field strength and the spin of its black hole (Agarwal et al 2017). Based on the measurements of its spectral lines (luminosity and line width) the mass of its central black hole has been estimated to be 10 8.9±0.5 M (Nilsson et al 2009;Gu et al 2001;Woo & Urry 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been categorized as an optically violent variable (OVV) revealing large and rapid polarized outbursts in optical bands on various timescales (days to years). Multifrequency radio light curves (4.8 have been used to study the core shift effect and to estimate the equipartition field strength and the spin of its black hole (Agarwal et al 2017). Based on the measurements of its spectral lines (luminosity and line width) the mass of its central black hole has been estimated to be 10 8.9±0.5 M (Nilsson et al 2009;Gu et al 2001;Woo & Urry 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field strength in the γ-ray emitting region is more or less similar to that in the pc-scale jet as estimated from the core-shift effect (e.g., Fromm et al 2013;Zamaninasab et al 2014;Agarwal et al 2017). In the jet core-shift studies, it was found that µ~-B R 1 within the region of radio cores (e.g., O'Sullivan & Gabuzda 2009;Sokolovsky et al 2011;Fromm et al 2013;Agarwal et al 2017). Assuming the magnetic field strength in the γ-ray emitting region, as constrained from the blazar SED fitting, roughly follows the magnetic field distribution as derived from the core-shift effect, using = -B B R 1 1 (B 1 is the magnetic field strength at 1 pc), we calculate position of the γ-ray emitting region g R for each source in our sample.…”
Section: Resultsmentioning
confidence: 54%
“…Due to the rough agreement of the magnetic field strength in the γ-ray emitting region and that of the radio core at the pc scale (e.g., Fromm et al 2013;Zamaninasab et al 2014;Agarwal et al 2017), we calculate the location of the γ-ray emitting region for these blazars by assuming that the magnetic field strength derived in the SED fitting follows the magnetic field strength distribution as derived from the radio core-shift measurements. The main results are summarized as follows.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the inferred variability here probes only the noise floor as opposed to intrinsic source based variability which often leads to indices in the range −1.5 − −2.5 (e.g. Mohan et al 2014, 2015, Agarwal et al 2017Goyal et al 2017 and references therein). The bending power law is the best fit model in the light curves of PKS 0235+164: 10-02-2002 and PKS 0528+134: 14-09-2009.…”
Section: Temporal Variabilitymentioning
confidence: 85%